2020
DOI: 10.2147/cmar.s249066
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Regulation of <em>RUNX3</em> Expression by DNA Methylation in Prostate Cancer</p>

Abstract: To investigate the role of DNA methylation in the regulation of Runt-related transcription factor 3 (RUNX3) and the effect of such mechanism on the proliferation of prostate cancer (PCa) cells. Materials and Methods: The methylation of the RUNX3 in the promoter region in PCa cells was detected by bisulfite-sequencing PCR (BSP). Following treatment of the PCa cells with DNA methylation transferase inhibitor 5-AZA-2ʹ-deoxycytidine (AZA), the effect on methylation level and expression of RUNX3 were analyzed by qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Upregulation of Runx3 can inhibit the proliferation and metastasis of gastric cancer and may serve as a new target for cancer therapy (Yu et al, 2017). Studies have reported that DNMT3B could regulate the expression level of Runx3 by altering the DNA methylation of Runx3 in prostate cancer cells involved in prostate cancer progression (Yang et al, 2020). MiR-148a may improve cell proliferation and invasion by regulating Runx3 expression through regulating DNMT3B dependent DNA methylation in gastric cancer, providing a new regimen for gastric cancer therapy (Zuo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of Runx3 can inhibit the proliferation and metastasis of gastric cancer and may serve as a new target for cancer therapy (Yu et al, 2017). Studies have reported that DNMT3B could regulate the expression level of Runx3 by altering the DNA methylation of Runx3 in prostate cancer cells involved in prostate cancer progression (Yang et al, 2020). MiR-148a may improve cell proliferation and invasion by regulating Runx3 expression through regulating DNMT3B dependent DNA methylation in gastric cancer, providing a new regimen for gastric cancer therapy (Zuo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can have a therapeutic effect on keloid by increasing the sensitivity of keloid fibroblasts to PaPDT [ 13 ]. Studies have shown that RUNX3 promoter hyper-methylation is a key factor in tumorigenesis and proliferation [ 14 , 15 ]. Meanwhile, downregulation of Zeste Homolog 2 (EZH2) can reduce the methylation level of RUNX3, and silencing EZH2 can inhibit the re-methylation of tumor cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%